The effect of scarcity messages and visual appeal on impulse buying among gen z shopee users in cirebon - Muhamad Reza Mubarok; Siska Ernawati Fatimah (Institute of Computer Science (IOCS), 2026)
The rapid growth of e-commerce, particularly the Shopee platform, has driven massive shifts in consumer digital shopping behavior through various marketing tactics. This study aims to analyze the partial and simultaneous effects of scarcity messages and visual appeal on impulse buying behavior among Generation Z Shopee users in Cirebon City. This study uses a causal associative design and a quantitative methodology. 150 respondents who were chosen using the purposive sampling technique were given questionnaires to complete in order to collect data. Using SmartPLS 4.0 software, structural equation modeling based on partial least squares (SEM-PLS) was used to analyze the data. The findings reveal that scarcity messages have a favorable and substantial impact on impulsive purchases, indicating that time and stock constraints generate psychological urgency for young consumers. Furthermore, visual appeal also exerts a favorable and substantial impact on, demonstrating that attractive platform interface aesthetics successfully stimulate consumers' positive emotional responses. Simultaneously, the combination of scarcity message strategies and visual appeal contributes a strong influence on the level of impulsive purchasing by 60.1%. These results highlight the significance of integrating visual stimuli and scarcity appeals for digital marketers in optimizing sales volume in developing regional markets